Post‐transplant Lymphoproliferative Disorders After Liver Transplantation: A Retrospective Cohort Study Including 1954 Transplants. Issue 8 (5th May 2021) - Tajima, Tetsuya; Hata, Koichiro; Haga, Hironori; Nishikori, Momoko; Umeda, Katsutsugu; Kusakabe, Jiro; Miyauchi, Hidetaka; Okamoto, Tatsuya; Ogawa, Eri; Sonoda, Mari; Hiramatsu, Hidefumi; Fujimoto, Masakazu; et al.
Abstract : Post‐transplant lymphoproliferative disorders (PTLDs) are life‐threatening neoplasms after organ transplantation. Because of their rarity and multiple grades of malignancy, the incidence, outcomes, and clinicopathological features affecting patient survival after liver transplantation (LT) remain unclear. We reviewed 1954 LTs in 1849 recipients (1990‐2020), including 886 pediatric (<18 years of age) and 963 adult recipients. The following clinicopathological factors were studied: age, sex, liver etiologies, malignancy grades, Epstein‐Barr virus status, performance status (PS), Ann Arbor stage, international prognostic index, and histopathological diagnosis. Of 1849 recipients, 79 PTLD lesions (4.3%) were identified in 70 patients (3.8%). After excluding 3 autopsy cases incidentally found, 67 (45 pediatric [5.1%] and 22 adult [2.3%]) patients were finally enrolled. Comorbid PTLDs significantly worsened recipient survival compared with non‐complicated cases ( P  < 0.001). The 3‐year, 5‐year, and 10‐year overall survival rates after PTLD diagnosis were 74%, 66%, and 58%, respectively. The incidence of PTLDs after LT (LT‐PTLDs) was significantly higher ( P  < 0.001) with earlier onset ( P  = 0.002) in children, whereas patient survival was significantly worse in adults ( P  = 0.002). Univariate and multivariate analyses identified the following 3 prognostic factors: age at PTLD diagnosis ≥18 years (hazard ratio [HR], 11.2; 95% confidence interval [CI], 2.63‐47.4; P  = 0.001), PS ≥2 at diagnosis (HR, 6.77; 95% CI, 1.56‐29.3; P  = 0.01), and monomorphic type (HR, 6.78; 95% CI, 1.40‐32.9; P  = 0.02). A prognostic index, the "LT‐PTLD score, " that consists of these 3 factors effectively stratified patient survival and progression‐free survival ( P  = 0.003 and <0.001, respectively). In conclusion, comorbid PTLDs significantly worsened patient survival after LT. Age ≥18 years and PS ≥2 at PTLD diagnosis, and monomorphic type are independent prognostic factors, and the LT‐PTLD score that consists of these 3 factors may distinguish high‐risk cases and guide adequate interventions.